2019
DOI: 10.3390/en12030427
|View full text |Cite
|
Sign up to set email alerts
|

A Parametric Study and Performance Evaluation of Energy Retrofit Solutions for Buildings Located in the Hot-Humid Climate of Paraguay—Sensitivity Analysis

Abstract: Nowadays, awareness concerning the need to use energy efficiently is increasing significantly worldwide, thus, improving the energy efficiency levels in the building sector has acquired high importance because of their energy saving potential. However, several intervention options are available to achieve high energy efficiency levels in buildings, and the choice must be made considering the efficiency of the solution and the costs involved. Considering this, the present research aimed to develop a parametric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…The authors in [30] compared various roof insulation layouts and achieved a reduction in energy consumption higher than 10%. Likewise, by considering four different roof configurations, the authors [18] found it possible to reduce the annual discomfort rate by 7.4% and the annual energy requirement by 37%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors in [30] compared various roof insulation layouts and achieved a reduction in energy consumption higher than 10%. Likewise, by considering four different roof configurations, the authors [18] found it possible to reduce the annual discomfort rate by 7.4% and the annual energy requirement by 37%.…”
Section: Discussionmentioning
confidence: 99%
“…A parametric study in hot-humid Paraguayan buildings [18] concluded that reinforcing exterior walls with 5 cm insulation may increase the annual comfort rate 7% and decrease the requirements of annual energy by 37%. Moreover, with WWR up to 15%, there is no need to improve glazing areas; simple shading devices can help increase natural ventilation rates, and thus comfort rates.…”
Section: Humid Tropical Regions In Americamentioning
confidence: 99%
“…Energy consumption for hot water preparation was not analyzed. For the climatic data of Warsaw, for room type (1), the heating season reduction is from the value of E K,H,0 = 46.0 to E K,H,n = 42.9 kWh/(m 2 •a), for room type (2) from E K,H,0 = 61.1 to E K,H,n = 56.0 kWh/(m 2 •a) and for room type (3) from E K,H,0 = 83.1 to E K,H,n = 72.2 kWh/(m 2 •a). For all cases, the lowest final energy value was for insulation type B.…”
Section: Final Energymentioning
confidence: 99%
“…Reducing energy consumption in existing buildings has now become one of the most critical challenges in building construction, not only in cold climate region [1,2]. Activities undertaken in the area of building's retrofitting focus mainly on improving the thermal insulation of external walls.…”
Section: Introductionmentioning
confidence: 99%